Pemikiran Tokoh - Tokoh Pendidikan Islam Klasik (Sejarah Keilmuan Islam Interdisipliner) - Mahendra Arif Rianto, Mahendra Arif Rianto; Afiful Ikhwan, Afiful Ikhwan (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2024)
Abstract: This Article will in-depth explore the views of classical Islamic education scholars and their relevance in shaping the people's framework of thinking. Understanding their thinking methods is an important foundation for achieving the desired social welfare. The main focus lies on the characteristics of Islamic religious education in the Abbasid era, including the concept of knowledge as rational (aqli) and inherited (naqli). The discussion involves educational curricula from elementary to high levels, highlighting the important role in developing holistic understanding. Overall, this journal reflects the intellectual heritage of classical Islamic scholars and their empowerment in directing the development of public thought. The research method applied in this research is a qualitative approach. This journal will summarize various sciences that developed during that period, including mathematics, astronomy, chemistry, physics, geography, medicine and philosophy. Furthermore, the thoughts of prominent figures such as Ibnu Sina, Ibnu Khaldun, Al-Ghazali, Al-Kindi, and Al-Khwarizmi received in-depth attention in the educational context. This journal not only records their contribution to the development of science, but also presents their views on Islamic religious education. By compiling these thoughts, this article becomes a comprehensive understanding of the intellectual foundations of that time. Through this in-depth analysis, readers can better understand the recognized scientific and educational legacy of classical Islamic thinkers, enriching their understanding of the intellectual developments of the period.